The Role of Financial Development and Manufacturing Sector Expansion on Emission Reduction for Sustainable Economic Development in the World’s Biggest Emitter Asia - Aisyah Fitri Yuniasih , Ika Yuni Wulansari , Siskarossa Ika Oktora (International Journal of Advanced Science and Technology, 2020)
Manufacturing has played an imperative role on world’s economic development even in Asia. Massive expansion of this industrialization impact, enforces Asia to be the world’s biggest emitter because of the presumption as the major determinant of Carbon dioxide (Saidi & Mbarek) emissions. Instead of expected to accelerate high economic growth, it has left a harmful impact which threaten our environment sustainability. On the other side, the effect of globalization stimulates the evolution of financial development with debatable impact on the environment. Some argues that financial development supplies additional funding to boost production economic of scale particularly in manufacturing sector resulting CO2 emissions enhancement. On the contrary, the others assumes that environmentally friendly technology supported by adequate financial development can stimulate efficient production process which can protect the environment. Therefore, this study aims to analyze the effect of manufacturing sector expansion and financial development on CO2 emissions in Asia during 2009-2018 by using System Different Generalized Method of Moment (Sys-GMM) dynamic panel model. This study result shows that financial development negatively effects CO2 emissions, moreover it can minimize negative effect of manufacturing sector expansion on CO2 emissions reduction in line with the actualization of the 13th goal of Sustainable Development Goals (SDGs)